DETERMINAN AKUNTABILITAS PELAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Pada Pemerintah Daerah se- Jawa Tengah) - Vinda Erryana; Hendri Setyawan (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2016)
This study aims to determine the factors that determine the Local Government Finance Accountability Reporting. Variabel Government Accountability Financial Reporting independently used in this study is the Fiscal Decentralization measured using Local Self-Reliance, Reliance Regions, the performance is measured using the ratio Effectiveness, Operational Expenditure Ratio, Ratio Shopping Capital and Regional Status. The dependent variable used in this study is the Local Government Finance Accountability Reporting measured using BPK Audit Report on the Financial Statements of Local Government in the form of an audit opinion. The samples were all over the city / regency in Central Java province with the study period between 2011-2013. Data were collected using purposive sampling. Based on these criteria, the total of 35 city / county elected as the population in this study. The analytical tool used is path analysis with SPSS version 16.0 Results of the study found that there is a significant positive effect between the Regional Autonomy and Accountability Financial Reporting Regions. Dependence area does not have a significant impact on Regions Financial Reporting Accountability. The effectiveness of significant negative effect on the Local Government Finance Accountability Reporting. Operating expenditure does not have a significant impact on Regions Financial Reporting Accountability. Capital spending has a significant positive effect on Regions Financial Reporting Accountability. Regional Status significant negative effect on Regions Financial Reporting Accountability. From the findings, we can conclude that the Regional Addiction and capital expenditures are a significant positive effect on Regions Financial Reporting Accountability. Regional and Operational Expenditure dependence there is no significant effect on the Local Government Financial Reporting Accountability however Effectiveness and Regional Status has a significant negative effect on Regions Financial Reporting Accountability.